THE EXON 5, 6, 7, 8 OF P53 MUTATIONS IN ORAL SQUAMOUS CELLS CARCINOMA - Rahayu, Retno P (Indonesian Journal of Tropical and Infectious Disease, 2012)
Genetic instability may underlie the etiology of multistep carcinogenesis. The altered p53 gene observed in tumors may represent the expression of such instability and may allow the accumulation of other gene alterations caused by multiple mechanism. p53 gene is the guardian of the genome, that is why we pay more attention to this gene. In this study, we evaluated the significance of p53 mutation in 55 patient with oral squamous carcinoma. Thirty among them underwent well-differentiated carcinoma, while the remaining 25 patientsunderwent poorly differentiated carcinoma. The mutations were detected by PCR-SSCP (Single strand Conformational Polymorphism) analysis in the region between exon 5 and exon 8. The results indicated that the p53 mutation in exon 5 (40%), exon 6 (28%), exon 7 (24%) and exon 8 (8%) were associated with poorly differentiated carcinoma, whereas mutation in exon 5 (10%), exon 6 (30%), exon 7 (40%) and exon 8 (20%) were associated with well-differentiated carcinoma. These observations suggest that p53 mutation in exon5, 6, and 7 have strong correlation with poorly differentiated in oral squamous carcinoma while well-differentiated level was related with mutation in exon 6,7 and 8.